Pengaruh Kualitas Produk Terhadap Minat Beli Ulang Dengan Kepuasan Pelanggan Sebagai Variabel Mediasi (Studi pada Warung Makan Tacibay Dinoyo Kota Malang) - Waris, Khoiril; Wahono, Budi; Suharto, M. Khoirul Anwarudin Broto (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research was conducted to determine the effect of product quality on repurchase interest through customer satisfaction. The method used in this study is a quantitative method with an explanatory type of research. The population of this study is Tacibay Food Shop customers with a sample of 60 respondents obtained using non-probability sampling techniques with a purposive sampling approach. This research uses Structural Equation Modeling (SEM) data analysis method with the help of SmartPLS 3.2.9 software. The results of this study show that product quality affects repurchase interest, customer satisfaction affects repurchase interest, product quality affects customer satisfaction, product quality affects repurchase interest through customer satisfaction. Keywords: Product Quality, Repurchase Interest, Customer Satisfaction